(untitled) - Hunter, Lloyd P. (Massachusetts, 1966)
In approaching this subject it has become to introduce the main consideration of semiconductor devices with a relatively lengthy presentation of background material which often amounts to a short course in solid-state physics, complete with an introduction to modern physics.
Keywords: Semiconductors,Chất bán dẫn